CONDITION OF GLUTATHIONE (GSH) METABOLISM SYSTEM AT ALLOTRANSPLANTATION OF EMBRYONIC MUSCULE TISSUE AT RATS - O.V. Kulibaba; S.A. Petrov (European Scientific Journal, ESJ, 2014)
This article presents the results of determination of the of reduced glutathione content, glutathione reductase and glutathione peroxidase during allotransplantation of the embryo muscle tissue. During the research there was carried out 2 kinds of surgery: 1st - allotransplantation of embryo muscle tissue; 2nd - surgery without replanting. To obtain embryos we used female rats from gestation 3-4 weeks. We took an abdominal muscle tissue from embryo that was hemmed to homologous tissue of the adult rat. The same procedure was carried out with femoral muscle tissue.It was found that allotransplantation of the embryo muscle tissue leads to an increasing of restored glutathione at day 7 of experiment in femoral and abdominal muscle of adult rat, leads the increasing of glutathione glutathione reductase activity in all researched tissues on day 7 of the experiment, except the femoral muscle of the adult rat. At experiment day 7 during surgery without replanting glutathione increased in femoral and abdominal muscle tissue, and activity of glutathione reductase increased only in the abdominal muscle, while activity of glutathione peroxidase in the abdominal muscle tissue decreased.